NORTHEAST CHINA AS A CONTACT ZONE IN POLISH AND SERBIAN TRAVELOGUES, 1900-1939 - Ewertowski, Tomasz (Institute of Slavic Studies, Polish Academy of Sciences, 2017)
Historically, Northeast China (Manchuria) was a border zone between China and nomadic peoples, as well as between Russian and Qing empires since the 17th century. In the second half of the 19th century and in the first half of the 20th century, a number of factors (penetration by foreign powers, collapse of the Qing Empire, revolution in Russia, Japanese expansion and demographic changes) transformed this area into “a contact zone” in the sense given by Mary Louise Pratt. The main focus of the article is the way in which this contact zone was described by Polish and Serbian travellers. Their can provide a special outlook, because Poland and Serbia did not participate extensively in the colonial penetration into China, however, Serbs and Poles travelled there, often representing Russian institutions. Therefore they were observing China as agents of imperial force, but they did not identify themselves fully with it. Our analysis of the image of Northeast China as a contact zone will be divided into three broad sections: 1) political and military expansion, 2) economic and demographic relations, 3) transcultural phenomena of everyday life.

Północno-wschodnie Chiny (Mandżuria) są historyczną granicą między Chinami a ludami wędrownymi, od siedemnastego wieku również między Rosją a imperium dynastii Qing. W drugiej połowie dziewiętnastego wieku, a zwłaszcza w pierwszej połowie dwudziestego szereg czynników (penetracja przez obce mocarstwa, upadek dynastii Qing, rewolucja w Rosji, ekspansja japońska i zmiany demograficzne) uczyniły z tego obszaru „strefę kontaktu” w rozumieniu Mary Louise Pratt. Głównym tematem artykułu jest sposób opisu strefy kontaktu przez polskich i serbskich podróżników. Ich dzieła dają bowiem szczególną perspektywę, gdyż Polska i Serbia nie uczestniczyły w kolonialnej penetracji Chin, jednakże Serbowie i Polacy podróżowali do Państwa Środka, często reprezentując rosyjskie instytucje. Z tego względu obserwowali Chiny jako reprezentanci imperium, jednak nie identyfikowali się z nim w pełni. Analiza obrazu północno-wschodnich Chin jako strefy kontaktu dzieli się na trzy sekcje: 1) ekspansja polityczna i militarna, 2) relacje ekonomiczne i demograficzne, 3) zjawiska transkulturowe w życiu codziennym.
Keywords: travel writing; podróżopisarstwo; China; Chiny; serbska literatura; Serbian literature; polska literatura; Polish literature; Northeast China; Manchuria; imagology; imagologia